Overexpression of ERF1-V from Haynaldia villosa Can Enhance the Resistance of Wheat to Powdery Mildew and Increase the Tolerance to Salt and Drought Stresses - Xing, Liping; Di, Zhaocan; Yang, Wenwu; Liu, Jiaqian; Li, Meina; Wang, Xiaojuan; Cui, Chaofan; Wang, Xiaoyun; Wang, Xiue; Zhang, Ruiqi; Xiao, Jin; Cao, Aizhong (Frontiers in Plant Science, 2017)
The APETALA 2/Ethylene-responsive element binding factor (AP2/ERF) transcription factor gene family is widely involved in the biotic and abiotic stress regulation. H. villosa (VV, 2n=14), a wild species of wheat, is a potential gene pool for wheat improvement. H. villosa confers high resistance to several wheat diseases and high tolerance to some abiotic stress. In this study, ERF1-V, an ethylene-responsive element-binding factor gene of the AP2/ERF transcription factor gene family from wild H. villosa, was cloned and characterized. Sequence and phylogenetic analysis showed that ERF1-V is a deduced B2 type ERF gene. ERF1-V was first identified as a Blumeria graminisb f. sp. tritici (Bgt) up-regulated gene, and later found to be induced by drought, salt and cold stresses. In responses to hormones, ERF1-V was up-regulated by ethylene and abscisic acid (ABA), but down-regulated by salicylic acid (SA) and jasmonic acid (JA). Over expression of ERF1-V in wheat could improve resistance to powdery mildew, salt and drought stress. Chlorophyll content, malondialdehyde (MDA) content, superoxide dismutase (SOD) and peroxidase (POD) activity were significantly differences between the recipient Yangmai158 and the transgenic plants following salt treatment. Furthermore, the expression levels of some stress responsive genes were differences after drought or salt treatments. Although ERF1-V was activated by the constitutive promoter, the agronomic traits, including flowering time, plant height, effective tiller number, spikelet number per spike and grain size, did not changed significantly. ERF1-V is a valuable gene for wheat improvement by genetic engineering.